Hydraulic Simulation of Leakage in Post-Earthquake Water Supply Pipeline Network and Its Algorithm Improvement - Tianyang Yu (Advances in Civil Engineering)
For the post-earthquake water supply pipeline network, the method of generating random numbers to determine the pipelines with leakage damage according to the earthquake damage rate is adopted. Select the most suitable seismic damage rate calculation model for this study. The proportion of different leakage points of pipelines with different pipe materials and interface forms summarized by Shi and O’Rourke from the actual earthquake damage is used to randomly sample the pipelines that cause earthquake damage, determine the leakage loss form of each leakage point, and use the corresponding leakage flow model and the leakage point area model for hydraulic analysis of the leakage of the post-earthquake pipeline network. The pressure-dependent nodal demand (PDD) model is added to the hydraulic analysis to avoid the problem of node negative pressure in the hydraulic analysis of low-pressure pipe networks. The linear search and backtracking algorithm was used to control the iterative step size of the nonlinear equations of the pipe network nodes, which ensures the global convergence of the low-pressure hydraulic analysis of the pipe network.